Positive coping styles and perigenual ACC volume: two related mechanisms for conferring resilience? - Holz, Nathalie E.; Boecker-Schlier, Regina; Jennen-Steinmetz, Christine; Buchmann, Arlette; Blomeyer, Dorothea; Baumeister, Sarah; Plichta, Michael M.; Schmidt, Martin H.; Meyer-Lindenberg, Andreas; Banaschewski, Tobias; Brandeis, Daniel; Laucht, Manfred (Social cognitive and affective neuroscience, 2016)
Stress exposure has been linked to increased rates of depression and anxiety in adults, particularly in females, and has been associated with maladaptive changes in the anterior cingulate cortex (ACC), which is an important brain structure involved in internalizing disorders. Coping styles are important mediators of the stress reaction by establishing homeostasis, and may thus confer resilience to stress-related psychopathology. Anatomical scans were acquired in 181 healthy participants at age 25 years. Positive coping styles were determined using a self-report questionnaire (German Stress Coping Questionnaire, SVF78) at age 22 years. Adult anxiety and depression symptoms were assessed at ages 22, 23 and 25 years with the Young Adult Self-Report. Information on previous internalizing diagnoses was obtained by diagnostic interview (2-19 years). Positive coping styles were associated with increased ACC volume. ACC volume and positive coping styles predicted anxiety and depression in a sex-dependent manner with increased positive coping and ACC volume being related to lower levels of psychopathology in females, but not in males. These results remained significant when controlled for previous internalizing diagnoses. These findings indicate that positive coping styles and ACC volume are two linked mechanisms, which may serve as protective factors against internalizing disorders.
Gesehen am 07.05.2019